(untitled) (Malay Literature, 2020)
This paper examines a collection of poems titled 77 Tuju: Siri Ingatan kepada Kawan [77 Aims: Reminders for Friends Series](2015) by Zaen Kasturi. This discussion underscores Zaen Kasturi’s tendency to advocate for introspection by asking questions about friendship. Zaen Kasturi’s introspection is studied using a theoretical viewpoint called Pengkaedahan Melayu [Malay Methodology], introduced by Hashim Awang. Malay Methodology also discusses an approach known as pendekatan seni (arts approach). This approach is deemed suitable for examining the strengths of Zaen Kasturi’s art as evident through the diction and metaphorical expression in his work. Zaen Kasturi’s careful selection of words in crafting his poems creates an aesthetic effect and a "colouring of language" that clearly identifies Zaen Kasturias an accomplished poet. The high quality and style of Zaen Kasturi’s metaphorical language and his ingenuity in creating new expressions and fresh, original idioms are unique attractions to draw attention to the issue of introspection. Diction and metaphor are not merely stylistic ornamentation but are intended to strengthen the link between vocabulary and implicit meaning. This group of poems does not disregard the importance of art in the sharing of meaning, especially of content with introspective value. Keywords: Malay methodology, arts approach, Zaen Kasturi, poem, diction, metaphor, implicit meaning